2013
DOI: 10.7567/apex.6.063003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ultrathin Fe–Co Layer Grown on Amorphous Co–Fe–B by In situ Reflective High-Energy Electron Diffraction

Abstract: The textured MgO(001) tunnel barrier grown on CoFeB is a fundamental building block for spintronic devices such as magnetic tunnel junctions. Although the insertion of an ultrathin Fe-Co layer between an MgO layer and a bottom CoFeB layer is a common technique for improving the magnetoresistance effect, the characteristics of this technique remain unclear. We systematically investigated the as-grown structure of Fe-Co by reflective high-energy electron diffraction and found that a highly textured MgO(001) is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…From similarity to the RHEED pattern reported in the previous systematic study, 10) we deduce that the observed diffraction pattern represents a bcc CoFe(110) structure. The observed thickness dependence is basically consistent with the findings of the previous work, 10) except that the polycrystalline structure was stabilized for the slightly thicker film (t CoFe = 2 nm).…”
supporting
confidence: 87%
See 3 more Smart Citations
“…From similarity to the RHEED pattern reported in the previous systematic study, 10) we deduce that the observed diffraction pattern represents a bcc CoFe(110) structure. The observed thickness dependence is basically consistent with the findings of the previous work, 10) except that the polycrystalline structure was stabilized for the slightly thicker film (t CoFe = 2 nm).…”
supporting
confidence: 87%
“…Note that the ultra-thin CoFe is amorphous in the asdeposited state because of diffusion of B atoms into the CoFe. 10) Thus, the CoFe layer is actually CoFeB with a low B concentration, which promotes solid-phase epitaxial growth from the interface with MgO(001) and consequently improves the MR ratio.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] A large TMR ratio is attributed to the large tunnel transmittance of the Δ 1 states of MgO and the highly spin-polarized Δ 1 states of bcc Fe-based FMs. 3,4,[15][16][17][18] In addition to the large TMR, MgO-based MTJs exhibit a large tunnel magnetocapacitance (TMC) effect at room temperature. [19][20][21] The TMC effect is a phenomenon in which the capacitance changes with the magnetic field in tunneling systems.…”
mentioning
confidence: 99%